2013
DOI: 10.1021/om400190q
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Silicon-Functionalized (Silylmethyl)silanes and α,ω-Dichlorocarbosilanes Using the TMOP (2,4,6-Trimethoxyphenyl) Protecting Group: (TMOP)Me2SiCH2Cl and (TMOP)2MeSiCH2Cl as Reagents To Introduce the ClMe2SiCH2, MeOMe2SiCH2, or Cl2MeSiCH2 Group by Nucleophilic Substitution at Silicon

Abstract: In this study, the synthetic potential of the 2,4,6-trimethoxyphenyl (TMOP)-substituted (chloromethyl)silanes (TMOP)Me 2 SiCH 2 Cl (1) and (TMOP) 2 MeSiCH 2 Cl (2) for the preparation of Si-functionalized (silylmethyl)silanes and α,ω-dichlorocarbosilanes (with skeletons consisting of alternate carbon and silicon atoms) was investigated. Compounds 1 and 2 were used as reagents to introduce the ClMe 2 SiCH 2 , MeOMe 2 SiCH 2 , or Cl 2 MeSiCH 2 group by nucleophilic substitution at silicon. The three-step synthet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In continuation of these studies, we have now succeeded in synthesizing a series of new 4-silacyclohexan-1-ones ( 1a – 1c ), 4-silacyclohexan-1-one oximes ( 2a – 2c ), 1,4-azasilepan-7-ones ( 3a – 3c ), 1,4-azasilepanes ( 4a – 4c ), and 2-bromo-4-silacyclohexan-1-ones ( 5a and 5b ) that contain the silicon protecting groups MOP (4-methoxyphenyl), DMOP (2,6-dimethoxyphenyl), or TMOP (2,4,6-trimethoxyphenyl). In previous studies, we have demonstrated that these three methoxy-substituted phenyl groups can be easily removed from the silicon atom of a given MOP-, DMOP-, or TMOP-silane via protodesilylation under very mild conditions to give the corresponding chloro- or methoxysilane . Thus, compounds 1a – 1c , 2a – 2c , 3a – 3c , 4a – 4c , 5a , and 5b can be regarded as versatile building blocks for synthesis that can undergo (i) a variety of transformations at their C-functional group and (ii) selective cleavage reactions of their Si–MOP, Si–DMOP, and Si–TMOP moieties.…”
Section: Introductionmentioning
confidence: 99%
“…In continuation of these studies, we have now succeeded in synthesizing a series of new 4-silacyclohexan-1-ones ( 1a – 1c ), 4-silacyclohexan-1-one oximes ( 2a – 2c ), 1,4-azasilepan-7-ones ( 3a – 3c ), 1,4-azasilepanes ( 4a – 4c ), and 2-bromo-4-silacyclohexan-1-ones ( 5a and 5b ) that contain the silicon protecting groups MOP (4-methoxyphenyl), DMOP (2,6-dimethoxyphenyl), or TMOP (2,4,6-trimethoxyphenyl). In previous studies, we have demonstrated that these three methoxy-substituted phenyl groups can be easily removed from the silicon atom of a given MOP-, DMOP-, or TMOP-silane via protodesilylation under very mild conditions to give the corresponding chloro- or methoxysilane . Thus, compounds 1a – 1c , 2a – 2c , 3a – 3c , 4a – 4c , 5a , and 5b can be regarded as versatile building blocks for synthesis that can undergo (i) a variety of transformations at their C-functional group and (ii) selective cleavage reactions of their Si–MOP, Si–DMOP, and Si–TMOP moieties.…”
Section: Introductionmentioning
confidence: 99%
“…In continuation of these studies, we have now succeeded in synthesizing a series of new 4-silacyclohexanones and (4-silacyclohexan-1-yl)amines that contain the silicon protecting groups MOP (4-methyoxyphenyl), DMOP (2,4-dimethoxyphenyl), or TMOP (2,4,6-trimethoxyphenyl). In previous studies, we have demonstrated that these protecting groups can be easily removed from the silicon atom via protodesilylation under mild conditions . Therefore, the Si–MOP, Si–DMOP, and Si–TMOP moieties can also be regarded as Si-functional groups.…”
Section: Introductionmentioning
confidence: 99%